Pitching effects of buoyancy during four competitive swimming strokes - Cohen, R. C. Z.; Cleary, P. W.; Harrison, S. M.; Mason, B. R.; Pease, D. L. (Journal of Applied Biomechanics, 2014)
The purpose of this study was to determine the pitching effects of buoyancy during all competitive swimming strokes—freestyle, backstroke, butterfly, and breaststroke. Laser body scans of national-level athletes and synchronized multiangle swimming footage were used in a novel markerless motion capture process to produce three-dimensional biomechanical models of the swimming athletes. The deforming surface meshes were then used to calculate swimmer center-of-mass (CoM) positions, center-of-buoyancy (CoB) positions, pitch buoyancy torques, and sagittal plane moments of inertia (MoI) throughout each stroke cycle. In all cases the mean buoyancy torque tended to raise the legs and lower the head; however, during part of the butterfly stroke the instantaneous buoyancy torque had the opposite effect. The swimming strokes that use opposing arm and leg strokes (freestyle and backstroke) had smaller variations in CoM positions, CoB positions, and buoyancy torques. Strokes with synchronized left-right arm and leg movement (butterfly and breaststroke) had larger variations in buoyancy torques, which impacts the swimmer`s ability to maintain a horizontal body pitch for these strokes. The methodology outlined in this paper enables the rotational effects of buoyancy to be better understood by swimmers, allowing better control of streamlined horizontal body positioning during swimming to improve performance.